ANALISIS KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK MELALUI LKPD UNPLUGGED PADA MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI DI KELAS IV SD - Mitraturahmah; Nikma Tulzahra; Neni Hermita; Rifqa Gusmida Syahrun Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the critical thinking skills of fourth-grade elementary school students through the use of worksheets based on the unplugged approach on the topic “Plants as a Source of Life on Earth.” The background of this study is the still-low level of students’ critical thinking skills, which is caused by monotonous instruction and a lack of interactive teaching materials. This study employed a quantitative descriptive approach with a sample size of 26 students. Data collection was conducted through a multiple-choice test designed based on critical thinking skill indicators, namely providing simple explanations, building foundational skills, drawing conclusions, providing further explanations, and formulating strategies and tactics. The results of the study indicate that students’ critical thinking skills fall into the high category across all indicators, with respective percentages of 91.35%, 88.46%, 98.08%, 90.38%, and 90.38%. The drawing conclusions indicator received the highest percentage, indicating the students’ ability to process and integrate information effectively. These findings suggest that the use of unplugged-based worksheets emphasizing active analysis, evaluation, and problem-solving activities can effectively support the optimal development of students’ critical thinking skills.